Student-Reported Classroom Climate Pre and Post Teacher Training in Restorative Practices - Weber, Constanze; Rehder, Merle; Vereenooghe, Leen (Frontiers in Education, 2021)
Restorative practices (RP) offer a means to establish positive and caring relationships and could thus foster the mental and scholastic development of students by improving classroom climate. This could benefit both students with and without special educational needs and disabilities (SEND), yet to date no studies evaluated these practices in inclusive educational settings. Here we report the findings of two consecutive studies: a pilot single-group pre-post (Study 1) and a non-randomised controlled study of RP training vs. no-intervention control condition (Study 2). Across both studies, 531 students (46.5% female) with a mean age of 11.43 years (SD = 1.27) enrolled in the study at pre-test, of which 13.9% had a confirmed diagnosis of SEND and a further 5.7% were considered by teachers to likely have SEND. School and classroom climate as well as victimisation experiences, emotional well-being and social inclusion of students were assessed using self-report questionnaires. Easy enrolment of schools and students at pre-test indicated that studies investigating the effects of RP training could be feasible. However, in part due to COVID-19 related school closures, student attrition rates of 90% and 77% were observed, for study 1 and study 2 respectively. In spite of observed improvements in classroom climate for the intervention group in Study 2, statistical analyses yielded no significant effects of the intervention and there were no moderation effects of students’ perceived inclusion and victimisation experiences. Together, these studies provide the first quantitative student data on implementing RP in an inclusive educational setting. We discuss our findings in light of the need for ideas on how to reduce attrition and also consider longer school-wide and single-class implementations of RP.